Liquid chromatography-electro spray ionization tandem mass spectrometry for simultaneous determination of Moexipril and its active metabolite Moexiprilat in human plasma - Elaziz, Omar Abd; Farouk, Maha; Tawakkol, Shereen; Hemdan, Ahmed; Shehata, Mostafa (European Journal of Chemistry, 2014)
A selective, sensitive, and rapid liquid chromatography-electro spray ionization tandem mass spectrometry method has been developed and subsequently validated for the simultaneous determination of Moexipril (MOX), and its active metabolite Moexiprilat (MOXT) in spiked human plasma, using Benazepril (BENZ) as an internal standard (IS). Various modes were tried and the Multiple Reaction Monitoring (MRM) mode was found the most suitable one. The two analytes and Benazepril (IS) were extracted from human plasma by simple protein precipitation using acetonitrile as the precipitating solvent. The stationary phase used was a C18 Sunfire column while water and acetonitrile at 0.1% formic acid (30:70, v:v) was used as a mobile phase. The flow rate used was 0.8 mL/min. Food and Drug Administration guidelines were followed for the method validation. The linearity range was found to be 0.5-100 ng/mL for MOX and 5-200 ng/mL for MOXT and the correlation coefficient was more than 0.9980 for each analyte. Results for accuracy and precision showed satisfactory results. Also the method was compared with reported HPLC method and no significant difference was found.